Empowerment of Madrasas in Fulfilling Indicators Child Friendly Learning: Pemberdayaan Madrasah Dalam Pemenuhan Indikator Pembelajaran Ramah Anak - Bakhtiar, Nurhasanah; Dewi Sri Suryanti; nurhayati; Rahayu Dwi Utami; Afdilah Zahrah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service aims to empower madrasas in fulfilling child-friendly learning indicators. The method used is PAR (Parcipatory Action Research), consisting of four stages, namely identifying community needs and potential, developing a mentoring plan, implementing actions and evaluating/reflecting. The targets of service are 22 madrasas in Pekanbaru City, consisting of 10 Raudhatul Athfal, 6 Ibtidaiyyah madrasas and 6 Tsanawiyah madrasas. The service activities began with training on child-friendly learning indicators for madrasa heads and teachers representing 22 assisted madrasas. The next stage is providing assistance to madrasas both offline and online. The results of service activities show a positive impact on assisted madrasahs of 87.5% in terms of increasing insight, motivation and commitment of madrasah heads and teachers to move towards child-friendly madrasahs. The next results showed that 86.5% of the assisted madrasas had implemented child-friendly learning 2 months after the training. This figure has exceeded the target of 78%.